Business and financial cycles in the Eurozone: Synchronization or decoupling - Jameel Ahmed; Sajid M. Chaudhry; Stefan Straetmans (University of Birmingham, Birmingham Business School, 2015)
This paper proposes a novel approach, based on probit framework, towards measuring business cycle synchronization for 9 eurozone economies. We find strong cross-country synchronization in both business cycles and financial cycles. Moreover, financial synchronization dominates business cycle synchronization in the eurozone, especially after the introduction of the single currency. For some peripheral country pairs, we even find some evidence of "de-coupling" business cycles relative to the core countries but the majority of marginal business cycle effects do not change much over time. The former observation supports the often heard plea for more Europe-wide macro-prudential regulation whereas the latter observation gives ammunition to those economists that always stressed that the euro zone architecture is unfinished business and that the conditions for an optimum currency area are not fulfilled.
Keywords: C25; E32; F44; 330